2016
DOI: 10.1038/srep38893
|View full text |Cite
|
Sign up to set email alerts
|

The biogeography of soil archaeal communities on the eastern Tibetan Plateau

Abstract: The biogeographical distribution of soil bacterial communities has been widely investigated. However, there has been little study of the biogeography of soil archaeal communities on a regional scale. Here, using high-throughput sequencing, we characterized the archaeal communities of 94 soil samples across the eastern Tibetan Plateau. Thaumarchaeota was the predominant archael phylum in all the soils, and Halobacteria was dominant only in dry soils. Archaeal community composition was significantly correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 59 publications
8
38
0
Order By: Relevance
“…This nding was in agreement with previous ndings from the research also conducted in the Qinghai-Tibetan Plateau, which showed that the dominant archaeal phylum was Thaumarchaeota, accounting for 79.27% of sequences [32]. Thaumarchaeota have been detected in a variety of habitats [48][49][50], and identi ed as a novel archaeal phylum in 2008 [48].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This nding was in agreement with previous ndings from the research also conducted in the Qinghai-Tibetan Plateau, which showed that the dominant archaeal phylum was Thaumarchaeota, accounting for 79.27% of sequences [32]. Thaumarchaeota have been detected in a variety of habitats [48][49][50], and identi ed as a novel archaeal phylum in 2008 [48].…”
Section: Discussionsupporting
confidence: 92%
“…The Qinghai-Tibetan Plateau (QTP), known as the "roof of the world" and "the third pole", is an important component of the terrestrial ecosystem, which provides many vital ecological services [30]. As one of the world's most vulnerable habitat, the QTP region has harsh environmental conditions and is highly sensitive to environmental disturbance, which could greatly impact the distribution of organisms, especially soil microorganisms [31][32][33]. The knowledge about their underground microorganisms have largely been studied [34][35][36], but the characteristics of rhizosphere microbiota, particularly archaeal communities are inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Archaeal generalists were overwhelmingly dominated by Nitrososphaeraceae (formerly described as Group 1.1b; Fig. 4), which is consistent with several studies [65,66]. We could further approve the wellknown pH preference of Group 1.1c for acidic forest soils [67].…”
Section: Generalistssupporting
confidence: 90%
“…From previous studies, it is clear that soil archaeal communities can vary in predictable ways along broad environmental gradients [10,11,[14][15][16], and between different habitats [17]. Our previous study [8] sampled archaea in both primary forest and agricultural environments on a broad scale across Malaysia, finding that soil pH played a major role in community composition.…”
Section: Introductionmentioning
confidence: 98%